Survei Polimorfisme Tetua untuk Pengembangan Panel CSSL Padi (Oryza sativa L.) dan Identifikasi Tanaman F1 - Mariana Susilowati; Panjisakti Basunanda; Wening Enggraini; Ma'sumah Ma'sumah; Kurniawan R. Trijatmiko (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Raising yield potential of modernindica varieties is essential to meet the increased demand ofrice production. This is due to increased human population,threats of climate change and degradation of agriculturalresources. The use of chromosome segment substitutionlines (CSSL) is more effective for identification of genesthose are useful for improvement of yield potential. The aimsof this study were to observe the morphological traitdifferences between recipient parent (var. Ciherang) andthree candidates of donor parent (var. Fatmawati and newplant type lines, i.e. B12743 and B11143D), to identifypolymorphic SSR markers among them and to verify F1individuals. Ciherang and B11143D showed significantdifferences on flowering time, plant height, flag leaf area,tiller number, productive tiller number, panicle length,spikelet number per panicle and 1,000 grain weight. The rateof SSR marker polymorphisms between Ciherang andB11143D was the highest, where 155 of 513 markers (30.2%)were polymorphic. Marker genotyping using threepolymorphic markers showed that 26 of 27 plants resultedfrom the cross of Ciherang х B11143D were F1. These F1plants could become the basis of CSSL panel that facilitatethe mapping of genes responsible for increasing the yieldpotential.